2014
DOI: 10.1086/674390
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tissue Expander—Related Infections: Perioperative Antimicrobial Regimens

Abstract: Contrary to the proven effectiveness of a single dose of perioperative antibiotics, the common use of local antimicrobial irrigation and prolonged postoperative oral antibiotics appears to be an inadequate component of our preventive armamentarium. Also, because methicillin-resistant staphylococcal and pseudomonal infections occurred approximately 60% of the time, at institutions that have observed an increase of these organisms, it may be prudent that perioperative antimicrobials target these microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
0
31
0
3
Order By: Relevance
“…However, several recent studies indicate that a small but significant proportion of these infections are caused by Gram-negative bacilli such as E. coli , P. aeruginosa , and Klebsiella species [38–40]. Non-tuberculous mycobacterial and polymicrobial infections are less common but are difficult to manage [41]. With a significant rate of, and changing epidemiology of, infection in this setting, infection prevention has become extremely important.…”
Section: Specific Syndromes/sites Of Infectionmentioning
confidence: 99%
“…However, several recent studies indicate that a small but significant proportion of these infections are caused by Gram-negative bacilli such as E. coli , P. aeruginosa , and Klebsiella species [38–40]. Non-tuberculous mycobacterial and polymicrobial infections are less common but are difficult to manage [41]. With a significant rate of, and changing epidemiology of, infection in this setting, infection prevention has become extremely important.…”
Section: Specific Syndromes/sites Of Infectionmentioning
confidence: 99%
“…Finally, in addition to the wide range of clinical presentations of breast implant infections, there is still debate on the best clinical management to achieve implant salvage with few randomized or controlled studies to identify best management practices [22].…”
mentioning
confidence: 99%
“…S . epidermidis are the most common coagulase-negative staphylococci, and have been described as the bacteria most frequently involved in SSI after breast operations [8]. However, many other authors reported S .…”
Section: Discussionmentioning
confidence: 99%